THE EXAMPLES, NON-EXAMPLES TECHNIQUE FOR TEACHING SPEAKING IN ENGLISH - Sofyan A Gani; Veni Nella Syahputri (Universitas Syiah Kuala, 2015)
The objective of this study is to find out whether there is a significant difference in speaking performance between students who are taught using the Examples Non-Examples Technique (ENET) and those who are taught using the Grammar Translation Method (GTM). To achieve the goal of this study, the experimental design method was used with an experimental class and a control class. The sample of study was a class of 45 students as the experimental class and another class of 45 students as the control class. The instruments used for the study were tests. The data was analyzed through statistical formula including finding the frequency distribution, range (R), class of data (K), class of interval (I), mean, standard deviation, and Z-score. The results showed that the Z-score pre-test of experimental and the control classes was 1.3 (Z countZ table) in which the Z table was 2.04. This means that there was no significant difference between the scores of both classes in pre-treatment. However, in post-treatment the Z-score for the experimental class and control classes was 5.1 (Z countZ table) which indicated that there was a significant difference between the experimental class and the control class in post-treatment. In conclusion, ENET can be applied as an alternative technique in teaching speaking. The research hypothesis (Ha) is also proven that the use of ENET provides a positive contribution for the development of students’ speaking performance.